THE BIBLE IN CONTEXTUAL THEOLOGICAL WORK IN INDONESIA - Timo, Ebenhaizer I Nuban; Putrawan, Bobby Kurnia (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2021)
This article describes the problem of how the Bible as the word of God is interpreted contextually for theology in Indonesia. The method used in this article is to explore contextual theological models and to have a reciprocal, constructive and dialectical dialogue between the Bible and dogma (the universal tradition) as well as the actual beliefs of the community (local traditions). The result of this research is that the meaning of God in the Bible will have a liberating and humanizing power if the meaning of God is not applied directly but in dialogue with the actual beliefs of the community where the Bible is read and preached.